2016
DOI: 10.1038/srep28524
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Co-existence of Female Thyroid and Breast Cancers in Hangzhou, China

Abstract: Thyroid and breast cancers (TC, BC) are common female malignant tumors worldwide. Studies suggest that TC patients have a higher BC risk, and vice versa. However, it has not been investigated quantitatively if there is an association between the space-time TC and BC incidence distributions at the population level. This work aims to answer this question. 5358 TC and 8784 BC (female) cases were diagnosed in Hangzhou (China, 2008–2012). Pearson and Spearman rank correlation coefficients of the TC and BC incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 74 publications
0
6
0
1
Order By: Relevance
“…The space‐time prediction of nitrate and phosphate concentrations was based on the BME theory (Christakos, ), which has been applied successfully in various fields, including water quality, air pollution, and epidemiology (e.g., Coulliette et al, ; Fei et al, ; Jiang et al, ). In the BME modeling context, let NP ( p ) be the spatiotemporal random field model (Christakos, ) representing nutrient (nitrate or phosphate) pollutant concentrations in China's near seas during 2015, where the vector p = ( s , t ) determines a point within the space‐time domain D , with s denoting geographical location and t time.…”
Section: Methodsmentioning
confidence: 99%
“…The space‐time prediction of nitrate and phosphate concentrations was based on the BME theory (Christakos, ), which has been applied successfully in various fields, including water quality, air pollution, and epidemiology (e.g., Coulliette et al, ; Fei et al, ; Jiang et al, ). In the BME modeling context, let NP ( p ) be the spatiotemporal random field model (Christakos, ) representing nutrient (nitrate or phosphate) pollutant concentrations in China's near seas during 2015, where the vector p = ( s , t ) determines a point within the space‐time domain D , with s denoting geographical location and t time.…”
Section: Methodsmentioning
confidence: 99%
“…2b). Previous studies have shown that the BC incidence distribution was spatially heterogeneous in Hangzhou (revealing an increasing incidence trend from the southern to the northern parts of the city) and temporally stable during the period 2008–2012 11, 21 , thus making it a suitable data set to be studied by the STOK and the STP techniques for the purpose of space-time modeling, estimation and mapping of the BC incidence distribution.
Figure 2( a ) BC incidence data histogram and ( b ) BC incidence data histogram after the data have been transformed as .
…”
Section: Methodsmentioning
confidence: 99%
“…Methodologically, the random field BC ( s , t ) is viewed as a collection of realizations (possibilities) of the BC incidence distribution, where the probability that each one of these realizations occurs is expressed by the BC incidence probability law (Gaussian or non-Gaussian). This BC model makes it possible to calculate various space-time properties of incidence distribution with reasonable accuracy 11 , 22 . In particular, the BC ( s , t ) incidence distribution is represented by 18 where is the so-called travelling random field model of BC incidence, and .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…No trabalho [Fei et al 2016], os autores propõem uma relação espaço-temporal dos casos de câncer de tireoide e de mama na cidade de Hangzhou, na China. Eles utilizam o critério integrativo de previsibilidade da doença para observar a relação entre os dois tipos de câncer nas bases de conhecimento que mapeiam a doença.…”
Section: Trabalhos Relacionadosunclassified